2010
DOI: 10.1007/s12274-010-1044-y
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical silver indium tungsten oxide mesocrystals with morphology-, pressure-, and temperature-dependent luminescence properties

Abstract: Highly hierarchical structures of silver indium tungsten oxide (AgIn(WO 4 ) 2 ) mesocrystals can be rationally fabricated via the microwave-assisted synthesis method by tuning the initial concentrations of the precursors. Photoluminescence spectra of hierarchical AgIn(WO 4 ) 2 mesocrystals were measured to investigate the correlation between the morphology, pressure, and temperature and their luminescence properties. The materials showed interesting white emission when excited by visible light of wavelength 46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Hu et al 84 demonstrated that AgIn(WO 4 ) 2 MCs exhibit a white emission in the visible region when excited by 460-nm light. Their photoluminescence (PL) strongly correlated with the surface nanostructures of outgrowths; a larger amount of outgrowths led to stronger emission intensities.…”
Section: Optical Properties Of Mcsmentioning
confidence: 99%
“…Hu et al 84 demonstrated that AgIn(WO 4 ) 2 MCs exhibit a white emission in the visible region when excited by 460-nm light. Their photoluminescence (PL) strongly correlated with the surface nanostructures of outgrowths; a larger amount of outgrowths led to stronger emission intensities.…”
Section: Optical Properties Of Mcsmentioning
confidence: 99%
“…To date, the integration of 1D nanounits into hierarchical structures is of special interest due to their peculiar properties and functional applications [5]. The synthetic strategies have involved the use of hydrothermal/solvothermal reaction [6,7], soft/hard template [8][9][10], structure-directing agent [11], and microwave radiation [12]. Among the many routes to self-assembled hierarchical structures, template-directed synthesis with soft templates, such as microemulsion [13], micelles [14], and gas bubbles [15], has been demonstrated an effective approach.…”
Section: Introductionmentioning
confidence: 99%
“…All these effects should be taken into account in order to understand the process characteristics in TEM. Owing to its potential applications in optical fibers, photocatalytic materials, and sensors, α-Ag 2 WO 4 has attracted considerable research and development attention 18 19 20 21 22 23 24 25 26 27 28 29 30 31 . By exposure to the electron beam of an electron microscope, the α-Ag 2 WO 4 undergoes in situ nucleation of Ag filaments on the crystal surface 16 17 32 , and the presence of these Ag nanoparticles leads to unique optical 33 and microbial properties 34 .…”
mentioning
confidence: 99%